Critical thinking and creativity in the Nigerian philosophy of education (2016)
Developing critical thinking and possessing exceptional human capacity far thought and creativity are part of the skills that can help to achieve the goals of education. As higher education and job requirements become competitive, complex and technical, proponents argue that students will need skills such as critical thinking and creativity to successfully navigate the modem world, excel in challenging careers, process increasingly complex information, etc. As a result, it is expedient to foster critical thinking and creativity in education. To prepare leaders to solve problems and develop societies in the 21" century, there is the need to develop them in how to use cognitive tools of critical thinking and creativity. Critical thinking involves examining possibilities carefully, fairly and constructively, while creativity has to do with exploring ideas, generating possibilities, looking for many right answers rather than just one. The paper philosophically carries out conceptual analysis of critical thinking and creativity as educational concepts. It explores what they entail, the characteristics of a critical thinker and creative person, the relationship between the two concepts, as well as their relevance to education for the transformation and development of Nigeria particularly in achieving the Nigerian philosophy of education. Recommendations were thereafter suggested. The paper concludes that critical thinking skills go hand in hand with creative skills therefore, it is when educators realise the relationship between the two that leaders’ capacity for innovation to develop the society can be enhanced